Participative Leadership and Shared Facility Management: An Integrated Model for Conducive Learning Environments - Rica Agus Budiyanto; Sri Handayani (Dinasti Publisher, 2025)
This study rigorously examines the implementation of participative leadership in the intricate context of shared facility management within multi-unit elementary school complexes, specifically focusing on the SDN Tegal Alur Complex. Employing a qualitative phenomenological approach, the research deeply probes the subjective experiences and perceptions of school principals, teachers, and administrative staff concerning interschool collaboration in resource allocation and maintenance. The investigation reveals a highly effective and robust operational model that synergistically integrates Rensis Likert's Participative Management Theory with W. Edwards Deming's Plan-Do-Check-Act cycle. This integrated framework's success is attributed to several key elements: active stakeholder participation in decision-making processes, which significantly fosters inclusivity and prevents conflicts; the establishment of transparent and responsive two-way communication channels; and the cultivation of a profound sense of ownership and collective responsibility among all parties, leading to voluntary maintenance and ethical usage. Furthermore, the pivotal